Experimental Investigation of the Flow Field in a Multistage Axial Flow Compressor - B. Lakshminarayana; N. Suryavamshi; J. Prato; R. Moritz (International Journal of Rotating Machinery)
The nature of the flow field in a three stage axial flow compressor, including a detailed survey at the exit of an embedded stator as well as the overall performance of the compressor is presented and interpreted in this paper. The measurements include area traverse of a miniature five hole probe (1.07 mm dia) downstream of stator 2, radial traverses of a miniature five hole probe at the inlet, downstream of stator 3 and at the exit of the compressor at various circumferential locations, area traverse of a low response thermocouple probe downstream of stator 2, radial traverses of a single sensor hot-wire probe at the inlet, and casing static pressure measurements at various circumferential and axial locations across the compressor at the peak efficiency operating point. Mean velocity, pressure and total temperature contours as well as secondary flow contours at the exit of the stator 2 are reported and interpreted. Secondary flow contours show the migration of fluid particles toward the core of the low pressure regions located near the suction side casing endwall corner.